Halal Tourism Village Potential Through Asset Based Community Development - Rachmiatie, Atie; Setiawan, Ferry; Yuningsih, Ani; Suja’i, Imam Sukwatus (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
Village tourism" and "halal tourism" are two concepts that are currently become the priority of government programs and the center of global attention. Combining these two concepts is not easy. With the Asset Based Community Development (ABCD) approach, this study aims to map the potential of Dayeuh Kolot Village, Subang Regency as an asset in implementing and developing halal tourism. This research uses descriptive qualitative methods, with interview and FGD data collection techniques. The focuses of this research are: first, to map the recognition and knowledge of the concept of halal tourism from the stakeholders.  Second, to identify tourist destinations as resources owned village. The results showed that the village’s potencies for supporting tourism had been identified, utilized, and initiated by authority of village leaders. The Village also has a fairly high potential of natural resource, but it has not meet the requirements of halal tourism industry standards. The village leaders, tourism actors and community groups are familiar and understand the concept of Halal Tourism Village, but were not ready to implement it. Socialization, collaboration, and appropriate regulations are still needed for Pentahelix stakeholders in rural areas for the development of halal tourism villages. As an implication of this research, it is necessary to strengthen the religious aspect, i.e., increased the understanding of Islamic law of the "halalness" of tourism products and services that are tangible, as well as intangible aspects of tourism such as cleanliness, honesty, tolerance and physical and psychological health.